Range expansion of Lymantria dispar dispar (L.) (Lepidoptera: Erebidae) along its north‐western margin in North America despite low predicted climatic suitability. (23rd November 2018) - Streifel, Marissa A.; Tobin, Patrick C.; Kees, Aubree M.; Aukema, Brian H.
Abstract: Aim: The European gypsy moth, Lymantria dispar dispar (L.), (Lepidoptera: Erebidae) is an invasive defoliator that has been expanding its range in North America following its introduction in 1869. Here, we investigate recent range expansion into a region previously predicted to be climatically unsuitable. We examine whether winter severity is correlated with summer trap captures of male moths at the landscape scale, and quantify overwintering egg survivorship along a northern boundary of the invasion edge. Location: Northern Minnesota, USA. Methods: Several winter severity metrics were defined using daily temperature data from 17 weather stations across the study area. These metrics were used to explore associations with male gypsy moth monitoring data (2004–2014). Laboratory‐reared egg masses were deployed to field locations each fall for 2 years in a 2 × 2 factorial design (north/south aspect × below/above snow line) to reflect microclimate variation. Rates of successful egg hatch were assessed the following springs. Results: Reductions in summer male moth captures are associated with several metrics of winter severity, such as minimum temperatures. Most egg masses suffered >95% mortality each winter. However, hatching success reached up to 80% in egg masses that had overwintered below the snow line (e.g., <30 cm from the ground). Main Conclusions: Our findings that cold winter temperatures are associated with reduced summer trap captures of European gypsy moth, likely due to increased overwintering mortality of exposed egg masses, are consistent with previous predictions of thermal range boundaries for this species. However, high survival in egg masses deposited close to the ground are consistent with thermal escape in subnivean environs (i.e., below snow cover), and suggest that further northward range expansion will be likely in areas that receive measurable annual snowfall.